Upaya Meningkatkan Minat dan Ketrampilan Menulis Vocabulary Bahasa Inggris di SMP Negeri 5 Meulaboh Aceh Barat - Rosita; Sri Ulfa Junaidah; Husaini; Agus Salim Nazar; Adnan; Umi Kalsum; Amiruddin; Salfiyadi, Teuku (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2022)
This study aims to improve writing skills in English by using a cooperative learning model to fill in the gaps in the text of a song. The expected indicator is that students are able to write vocabulary in English. This research method is Classroom Action Research. The object of this research is writing skills through the cooperative learning model to fill in the gaps in the text of a song while the research subjects are students of class VII/C SMP Negeri 5 Meulaboh. students still have errors in writing vocabulary. Therefore, the cooperative learning model of filling in the gaps in the text of a song can improve vocabulary writing skills in English and can also increase students' enthusiasm for learning.